Acceptability of Violence Against Women Among the Roma Population in Spain - Vives-Cases, Carmen (Journal of interpersonal violence, 2021)
Acceptability of violence against women (VAW) is a key dimension in addressing this social problem, given its influence on both the violent conduct of aggressors and the decisions of affected women. This study analyzes, for the first time, the magnitude of acceptability of VAW and associated factors in the Roma population in Spain. The Roma population is the largest ethnocultural minority in Europe. Data were analyzed from the Spanish National Health Survey of the Roma Population of 2014, a survey of 1,167 people identified as members of the Roma community. The results indicate that 70.9% of those surveyed completely reject VAW, with lower probability of acceptability among women than men (odds ratio [OR]: 0.66; 95% confidence interval [CI]: [0.51, 0.86]). There is also a decrease in probability as income increases, in people who identify themselves as evangelical (OR: 0.5; 95% CI: [0.36, 0.71]) and among those who report being acquainted with a battered woman (OR: 0.68; 95% CI: [0.48, 0.97]), similarly in women and men. It has to be highlighted that the observed associations between socioeconomic conditions and acceptability of VAW should be considered when designing strategies for raising awareness about the consequences of VAW for the Roma population.